Teknik Penyembunyian Data Non-Destruktif pada Citra Digital Menggunakan Metode End-of-File (EOF) dan Enkripsi AES-256 - Muhammad Ulya Farhan; Fathul Barri Akbar; Ammar Fatin; Ariifah Yaasir Harahap (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
Conventional cryptography and LSB steganography often suffer from detectability and visual distortion. This study proposes a non-destructive solution integrating End-of-File (EOF) steganography with AES-256 encryption to ensure data security without compromising carrier media quality. The method functions by appending encrypted data after the image file terminator, leaving the original pixel structure intact. Security is reinforced using AES-256 (CBC mode) and PBKDF2-HMAC-SHA256 with 100,000 iterations. Experimental results using the